Influence of dental care for infants on caries prevalence: A comparative study - Melhado, Fabiola Lemos; Cunha, Robson Frederico [UNESP]; Nery, Rosangela Santos (My University, 2003)
Purpose: The influence of early dental care on the prevalence of dental caries was determined in children ages 35 to 40 months divided into 2 groups of 160 children each, with 1 group participating in a dental care program from the first year of life to the time of the study, while the other group did not receive any dental care. Methods: The clinical conditions considered for the evaluation were: sound teeth, enamel caries without cavitation, enamel caries with cavitation, and dentinal caries. The proportion and chi-square tests were used for statistical analysis with the level of significance set at 5%. Results: A significant difference regarding the presence of dental caries, especially in the number of children presenting enamel caries with cavitation (P<.0001), was observed between the 2 groups. The number of children with enamel caries without cavitation and dentinal caries was similar for the 2 groups. Conclusions: Considering the aspect of dental caries prevention, the authors concluded that children in the age range of 3 to 4 years who received early dental care showed better oral conditions.
Keywords: Caries prevalence; Dental caries; Infant oral health; chi square distribution; child; comparative study; controlled study; dental care; dental caries; dentin; enamel; evaluation; female; health program; human; major clinical study; male; mouth hygiene; prevalence; statistical analysis; classification; infant; pathology; preschool child; Chi-Square Distribution; Child, Preschool; Dental Care for Children; Dental Caries; Dental Enamel; Dentin; Female; Humans; Infant; Male